Incorporation of fruits or fruit pulp into yoghurts: recent developments, challenges, and opportunities - Hasitha Priyashantha; Ranga Madushan; Samanthi W. Pelpolage; Anuradha Wijesekara; Shishanthi Jayarathna (Frontiers in Food Science and Technology)
The incorporation of fruits and/or fruit pulps into fermented dairy products has gained substantial interest in the food industry, driven by consumer demand for functional foods that combine health benefits with natural ingredients. This value addition enhances plain yoghurts with antioxidants, dietary fiber, bioactive compounds, and probiotics, delivering potential health benefits such as immune modulation, gut health improvement, and reduced risks of metabolic disorders. Fruit components interact with the macromolecular structure of yoghurt, influencing its physicochemical properties, texture, and sensory attributes. Organic acids modulate protein gelation and emulsification, polyphenols alter protein aggregation and antioxidant stability, and dietary fibers enhance water-holding capacity and probiotic viability. These interactions significantly impact yoghurt’s structure, stability, and functional benefits, necessitating an understanding of their mechanisms. Fruits such as pomegranate, passion fruit, and açaí pulp have demonstrated antioxidative and cardioprotective properties, while innovations in incorporating fruit peels and seeds, such as passion fruit peel flour and grape skin, enhance physicochemical stability and nutrient density. Beyond these advantages, challenges such as increased syneresis, altered pH, reduced probiotic viability, and microbial contamination during storage persist. This review critically evaluates the impact of fruit incorporation into yoghurt, examining its effects on probiotic viability, physicochemical properties, sensory attributes, and microbiological stability. Achieving an optimal balance requires careful selection of fruit sources, processing strategies, and formulation techniques to sustain probiotic viability and yoghurt stability throughout its shelf life. By synthesizing recent research, this review highlights both the challenges and opportunities in developing fruit-enriched yoghurts, emphasizing strategies to optimize processing techniques and preserve key quality attributes. The findings offer a scientific framework for developing innovative, health-promoting, and shelf-stable fruit-enriched yoghurts, aligning with evolving market demands and functional food advancements.